Heterotrimeric G-protein subunit Gαi2 contributes to agonist-sensitive apoptosis and degranulation in murine platelets - Cao, Hang (2018)
Gαi2, a heterotrimeric G-protein subunit, regulates various cell functions including ion channel activity, cell differentiation, proliferation and apoptosis. Platelet-expressed Gαi2 is decisive for the extent of tissue injury following ischemia/reperfusion. However, it is not known whether Gαi2 plays a role in the regulation of platelet apoptosis, which is characterized by caspase activation, cell shrinkage and cell membrane scrambling with phosphatidylserine (PS) translocation to the platelet surface. Stimulators of platelet apoptosis include thrombin and collagen-related peptide (CoRP), which are further known to enhance degranulation and activation of αII bβ3-integrin and caspases. Using FACS analysis, we examined the impact of agonist treatment on activation and apoptosis in platelets drawn from mice lacking Gαi2 and their wild-type (WT) littermates. As a result, treatment with either thrombin (0.01 U/mL) or CoRP (2 μg/mL or 5 μg/mL) significantly upregulated PS-exposure and significantly decreased forward scatter, reflecting cell size, in both genotypes. Exposure to CoRP triggered a significant increase in active caspase 3, ceramide formation, surface P-selectin, and αII bβ3-integrin activation. These molecular alterations were significantly less pronounced in Gαi2-deficient platelets as compared to WT platelets. In conclusion, our data highlight a previously unreported role of Gαi2 signaling in governing platelet activation and apoptosis.